Specific Activities of Public Authority Bodies in Emergency and Crisis Situations - Velichko, Larysa; Kashchenko, Dmytro (Theory and Practice of Public Administration, 2023)
This article is devoted to consideration of the peculiarities of the activities of public authorities in emergency and crisis situations. It was determined that crisis and emergency management is a cyclical process. The various stages include assessment, planning, preparation, mitigation, response, transition to recovery and final assessment; and careful evaluation and consideration of lessons learned can increase sustainability in the future. It is noted that there is no zero risk in any activity. No matter how marginal it may be, there is always some degree of risk involved. Every activity we do in life involves risk, and the difference is that we accept those risks after a cost-benefit or rational choice analysis and assign them relative priorities.It is emphasized that as soon as a threat manifests itself or a critical incident exceeds the capabilities or resources of the organization, there is a need to respond. The guiding principles of this process are developed at the planning and preparation stage of the crisis and disaster management cycle. This includes public-private partnerships as well as working with alternative stakeholders such as non-governmental organizations, charities, voluntary groups and the public. Effective provision of such interaction is possible through the use of the so-called C7 Doctrine.The elements of an effective response to the crisis were identified: maintaining reputational integrity; smart planning and preparedness; strong leadership; effective and timely communications; strategic, well-organized interdepartmental cooperation; strategic allocation of resources; successful operational tactics; post-crisis assessment and learning to improve on any mistakes made along the way. It has also been established that during a critical incident or crisis event, there are two main requirements for their resolution: an organization that must respond adequately, and a leader who directs the efforts of this organization.